IMPACT OF VISUAL CUES IN ONLINE READYMADE GARMENT STORES: A NEUROMARKETING PERSPECTIVE - Chib, Shiney; Dhengle, Dinesh (International Journal of Research -GRANTHAALAYAH, 2025)
This study examines how customer behaviour is affected by visual signals based on neuromarketing in the setting of online ready-made clothing retailers. Visual stimuli are essential for drawing in customers, evoking strong feelings, and influencing their intents to make a purchase, especially as the significance of digital experiences in e-commerce continues to expand. The study examines how consumers react to features including high-quality product photos, colour schemes, models, website layout, interactive views, and self-image features like virtual try-ons using a descriptive research approach and a structured questionnaire given to 200 respondents. Strong visual signals and consumer decision-making behaviour are significantly positively correlated, according to the results, which are statistically confirmed by an independent samples t-test. Based on neuromarketing concepts, the findings provide e-retailers with useful insights to improve user engagement and conversion rates through smart visual display.